Adaptation Hikayat Merong Mahawangsa Text to Film: Comparative Analysis of Narrative Elements: (Adaptasi Teks Hikayat Merong Mahawangsa kepada Filem: Analisis Perbandingan Unsur Naratif) (Melayu: Jurnal Antarabangsa Dunia Melayu, 2015)
The main objective of this study is to compare the movie Hikayat Merong Mahawangsa with the literary text, i.e. Hikayat Merong Mahawangsa, in terms of the narrative elements of plot, character, setting, writing style and themes, in order to study the existence of similarities and differences between the movie and the literary work, and to analyse the type and method of adaptation employed by the director and screenwriter of the movie. To achieve this objective, the theory of adaptation of Desmond and Hawkes was used to compare the specified narrative elements. This study was conducted through a combination of library research, interviews, textual analysis, and information search on the internet. The study finds that the screenwriter and film director adaptation was in fact a loose on, in which most of the narrative elements found in the original text were altered or reinterpreted. In fact, there are a number of elements that were added or dropped by the screenwriter and director. All this was done to suit the movie`s storyline which, on the whole, is interesting and effective. Elements of logic dominate the film even though Hikayat Merong Mahawangsa itself is full of myths and legends. This study is significant because it contributes towards the understanding of the complexity and dynamics of the thought of the director and screenwriter in adapting a literary work into film in an effort to highlight the level of talent in the Malay film industry.Keywords: adaptation, film, literary history, Hikayat Merong Mahawangsa, narrative elements